Gut microbiota dysbiosis impairs TGF-β/Smad4 signaling to drive postoperative metastasis in colorectal cancer - Lan, Tongtong; Hou, Qilong; Zhao, Huichao; Luan, Yiman; Shi, Yuying; Hu, Shengrui; Wang, Ningrui; Yan, Shiyu; Gong, Xinyi; Song, Yang (Frontiers in Microbiology, 2025)
BackgroundAfter surgical intervention, metastasis remains the primary contributor of mortality rates in colorectal cancer (CRC). While compelling evidence implicates gut microbiota dysbiosis as a key driver of CRC progression, its role in postoperative metastasis remains unclear.MethodsA total of 97 participants were recruited, comprising 21 postoperative CRC patients with metastasis (M group), 37 postoperative CRC patients without metastasis (C group), and 39 healthy individuals (H group). Fecal microbiota composition, short-chain fatty acid (SCFA) concentrations, and serum cytokines were quantified. Spearman correlation was used to assess the relationship between microbiota and SCFAs. Fecal microbiota transplantation (FMT) was performed by transferring patient specimens into antibiotic-pretreated orthotopic CRC mice models. Epithelial-mesenchymal transition (EMT) markers and TGF-β/Smad4 signaling were subsequently analyzed.ResultsIn humans, M group patients exhibited significant gut dysbiosis, characterized by enriched Fusobacterium and depleted Gemmiger, concomitant with markedly diminished fecal butyrate, propionate, and acetate (vs. H group, p < 0.05). In these patients, this dysbiosis was directly correlated with SCFA depletion (Padj < 0.05). Serologically, patients in the M group exhibited elevated TGF-β while suppressed IL-10 compared to C group (p < 0.05). In the mouse model, the FMT from M group significantly increased Fusobacterium abundance and reduced fecal acetate/butyrate, concomitantly accelerating tumor progression with elevated hepatic and cecal tumor weights and upregulated EMT markers (N-cadherin and MMP9). This pro-metastatic phenotype was associated with downregulated hepatic mRNA expression of the key SCFA receptors, FFAR2 and FFAR3. Notably, in the animal model, the FMT-M group exhibited elevated hepatic TGF-β and a trend toward reduced Smad4 expression, suggesting a potential dysregulation of the TGF-β/Smad4 signaling pathway. Conversely, the fecal microbiota from C group markedly suppressed Fusobacterium colonization and restored acetic acid, butyric acid levels which ameliorates pathological changes by attenuating N-cadherin expression and normalizing TGF-β/Smad4 signaling.ConclusionGut microbiota dysbiosis and SCFA depletion exert profound regulatory effects on postoperative CRC metastasis, potentially by promoting EMT through mechanisms involving the TGF-β/Smad4 signaling axis. Thus, targeting gut microbiota may offer promising therapeutic strategies to mitigate CRC metastasis.